Kalihinol analog MED6-189: a promising pan-antimalarial candidate - Le Roch, Karine (Henry Stewart Talks, 2026)
Antimalarial drug discovery, Natural product analogues (Kalinol), Drug-resistant Plasmodium falciparum, Mechanism of action studies, Apicoplast targeting, Vesicular trafficking pathways, Semi-synthetic compound (MED6-189), Preclinical development and translational challenges